Potential of green water meal as an ingredient in the formulation of diet for juvenile pacific white shrimp, Litopenaeus vannamei - Najamuddin Abdul Basri (2015)
Steady increase of fishmeal price due to unreliable supply of fishmeal in the world market, coupled with increased demand have led aquaculture nutritionist to search for cheaper and sustainable alternative protein sources that can be incorporated in formulated diets. Green water which consists of green microalgae (mainly Chlorella sp.) can be produced easily in freshwater fish culture tank. Dried green water or green water meal GWM contains relatively high crude protein making it a potential candidate for fishmeal substitution. In the present study, the potential of GWM as a substitute of fishmeal in the diets of Pacific white shrimp (Litopenaeus vannamei) was evaluated through two feeding trials. In Feeding Trial 1, five isoproteic and isolipidic diets with 0% (control diet), 10% (GWM10), 20% (GWM20), 30% (GWM30) and 40% (GWM40) GWM replacing fishmeal protein were fed to triplicate groups of shrimp, with an average initial weight of 1.73±0.003g and cultured in a flow-through tank culture system. The shrimps were fed by hand three times daily with amount 7-10% of their body weight for 44 days. In general, growth of the shrimp decreased with increasing level of GWM substitution. Although the 10% replacement of GWM (GWM10) caused significantly lower final body weight (FBW) and weight gain (WG) (P<0.05) compared with the control diet, the dry feed intake (DFI), feed conversion ratio (FCR), and specific growth rate (SGR) of this diet were not statistically different (P>0.05) from the control diet. In Feeding Trial 2, diets were formulated using the same specification with diet’s formulation in Feeding Trial 1 and fed to bigger size shrimps with an average initial weight of 6.42±0.02g and fed at 5-7% of their body weight daily for 56 days to investigate if larger shrimp has better tolerance than the smaller shrimp to GWM as dietary protein source. Similar growth trend with Feeding Trial 1 was observed in this trial. However, shrimp fed diet GWM10 did not show any significant differences in FBW (16.88±0.18g), WG (161.14±3.07%), SGR (1.50±0.04%/day), DFI (19.68±0.04g) and FCR (1.89±0.04) from the control diet, indicating an improved utilization of GWM compare to the findings in the Feeding Trial 1. Survival rates in both trials were high (above 95% in Feeding Trial 1 and above 88% for Trial 2) and not affected by the dietary treatments. The whole-body proximate compositions of shrimp fed experimental diets were significantly influenced by the inclusion of GWM with no definite trend in Feeding Trial 1. However, in Feeding Trial 2, the wholebody protein and lipid of the shrimps decreased with the increasing GWM level in the diets. Both trials proved that inclusion of GWM in the diets (GWM10, GWM20, GWM30, and GWM40) produced shrimp with more intense red/orange colour and contained higher total carotenoid concentration compare with the control diet. The present findings suggest that GWM is an acceptable alternative protein source for shrimp which can be included in the diet of Pacific white shrimp at a level of about 10% with advantage of providing carotenoid which will enhance the shrimps colour. Considering GWM as a by-product in an aquaculture system, cost of feed production for shrimp culture can be reduced with the inclusion of GWM in the diets.